IMPLEMENTATION OF FINITE STATE MACHINE (FSM) IN ARABIC LANGUAGE EDUCATION 3D GAME - Annubaha, Chakim (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
Arabic is the language used in the Koran, Hadith, and various sources of Islamic Knowledge. Therefore, mastering Arabic is very important in studying Islam. However, there are many obstacles to learning Arabic due to the complexity of its structure and limited media to facilitate learning. Therefore, media is needed to facilitate learning Arabic by taking advantage of current technological advances, including the Artificial Intelligence (AI) game. This study is based on the fundamental question that how to use computer game technology for learning Arabic, as well as how the effectiveness of the Finite State Machine (FSM) method to improve the quality of the learning games. The results of the implementation and testing show that the FSM method runs according to the plan and make the game more natural and attractive. This can be observed when playing the game. The player character animation can change based on the if-then variable met. If benar >=3 && uang = 1000, the game character changes to a Muslim shirt player animation. Thus, according to the conditions met, it can be said that the FSM method is suitable to be applied to the player character animation controller in this game.